Financial Management Information System Design with Business Intelligence Approach - Ardiansyah Putra; Muhamad Alda (Indonesian Journal of Data Science, IoT, Machine Learning and Informatics, 2025)
This research aims to design and develop a web-based financial management application for Pabrik Opak Sun Jaya Mandiri, focusing on financial management. Prior to the application’s development, the business used a manual financial management system, which led to various issues, such as unstructured transaction records, difficulties in monitoring cash flow in real-time, and slow financial reporting prone to human errors. These problems could hinder the business owner from making accurate financial and operational decisions.To address these issues, the application was developed using the PHP programming language and MySQL database, designed to automate the recording of rental transactions, income, and expenses in an integrated manner. The application includes features for automatic and real-time financial reporting, enabling the business owner to monitor financial conditions more accurately and efficiently. Additionally, it implements a Business Intelligence (BI) approach, providing analysis of financial data, including income and expense trends, as well as business performance over time.The research results indicate that the application effectively resolves the issues present in the previous financial management system, particularly in terms of efficiency, recording accuracy, and faster, more detailed data presentation. The business owner can better monitor financial developments, and employees find it easier to perform tasks such as report preparation and transaction recording. Continuous evaluation and feature updates are highly recommended to ensure the application evolves in line with the increasingly complex needs of the business. Therefore, this application is expected to have a long-term positive impact on the financial management of Pabrik Opak Sun Jaya Mandiri.